ENTERPRISE PENERAPAN ENTERPRISE ARCHITECTURE UNTUK SISTEM INFORMASI PENGARSIPAN PADA KANTOR KECAMATAN GADINGREJO: PENERAPAN ENTERPRISE ARCHITECTURE UNTUK SISTEM INFORMASI PENGARSIPAN PADA KANTOR KECAMATAN GADINGREJO - afrizal martin martin; Suprapto Suprapto; Mardiyanto (Jurnal Informatika Software dan Network (JISN), 2024)
In the current era of reform, human dependence on data technology continues to increase, with the use of internet access continuing to become widespread. a small part of the government system, to be able to follow technological developments and continue to improve performance skills in managing data, such as message archiving has a significant position in an institution and is used to support the activity process carried out by the institution. With this archiving system, it can be easier to process and speed up the management of incoming and outgoing message information and can store messages digitally and make it easier for civil staff at the Gadingrejo sub-district office to search for incoming and outgoing messages on a web basis. using the Enterprise Architectural Planning (EAP) method, with the aim of archiving documents based on this website, it is attempted to help facilitate the process of storing message documents and help make it easier for institutions to search for incoming and outgoing messages whenever needed in a short time, therefore the system This really helps institutional staff at the Gadingrejo sub-district office in carrying out work most efficiently and effectively so that it can be implemented. procedures for collecting information using methods, observation, library research, interviews. Based on reviews from Enterprise Architectural Planning Archives Management at the Gadingrejo District Office, the research hopes that the system created can help and simplify the process of storing, searching and document messages that are not easily lost.Keywords: EAP, Website, Incoming and Outgoing Mail, Gadingrejo District